1982
DOI: 10.1557/proc-15-455
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Effects in the Storage and Disposal of Radioactive Ion-Exchange Resins

Abstract: Research Is under way to characterize the effects of selfirradiation on radwastes which may be generated when organic ion-exchange media are used in water demineralization or decontamination operations at nuclear facilities. External factors affecting the relation between laboratory evaluations and field performance are emphasized• Initial experiments do not yet indicate substantial radiation dose-rate effects on radiolytic gas yields or acid product formation, when (fully swollen) sulfonic acid resins are irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…Conversely, cation exchange resins were more stable than anion resins up to an absorbed dose of 1 MGy (Alian et al, 1984). Resins with aromatic structure or under salt forms were more gamma resistant than aliphatic ones (Swyler et al, 1983a;Nikashina et al, 1959;Dessouki et al, 1989;Mohorčič et al, 1974). The use of salt forms of resins was found to be effective in inhibiting the γ-radiation damage (Ichikawa and Hagiwara, 1973;Alian et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Conversely, cation exchange resins were more stable than anion resins up to an absorbed dose of 1 MGy (Alian et al, 1984). Resins with aromatic structure or under salt forms were more gamma resistant than aliphatic ones (Swyler et al, 1983a;Nikashina et al, 1959;Dessouki et al, 1989;Mohorčič et al, 1974). The use of salt forms of resins was found to be effective in inhibiting the γ-radiation damage (Ichikawa and Hagiwara, 1973;Alian et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…Several papers in the literature have shown that radiation damage of ion exchange resins could depend on the absorbed dose, the dose rate, and the irradiation atmosphere, and that the combination of these factors leads to different results according the nature of the resin, used pure or in mixed bed. Moreover, several studies (Pillay, 1986;Gangwer et al, 1977;Swyler et al, 1983a;Ichikawa and Hagiwara, 1973) reported that gamma irradiation at doses exceeding 0.1 MGy mainly altered the properties of ion exchange resins (principally the anion resins). Gamma rays led to direct radiolysis of these resins, resulting in the scission of functional groups and the formation of radical products, or to an indirect radiolytic effect through interactions, which could occur between the resin and its degradation products.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations